Pewarisan Hukum Adat Minangkabau Ditinjau Dari Kompilasi Hukum Islam dan Kitab Undang-Undang Hukum Perdata - Aliya Sandra Dewi (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2023)
This article discusses the inheritance of Minangkabau customary law from the perspective of the Compilation of Islamic Law and the Civil Code. The research method used is a qualitative research method with a literature and statutory approach. Data were obtained from written sources such as books, articles, journals, documents and related literature. Qualitative data analysis techniques such as content analysis, grounded theory, and thematic analysis are used to understand the meaning and patterns of the data collected. This article provides an in-depth understanding of how Minangkabau customary law is inherited and practiced and how the Islamic Law Compilation and the Indonesian Civil Code have influenced the practice of Minangkabau customary law. The results of this research are expected to contribute to the development of Minangkabau customary law thinking and how to integrate customary law with applicable laws and regulations.Keywords: Customary Law; Islamic Law Compilation; Code of Civil law Abstrak: Artikel ini membahas tentang pewarisan hukum adat Minangkabau yang dilihat dari perspektif Kompilasi Hukum Islam dan Kitab Undang-Undang Hukum Perdata. Metode penelitian yang digunakan adalah metode penelitian kualitatif dengan pendekatan literatur dan peraturan perundang-undangan. Data diperoleh dari sumber-sumber tertulis seperti buku, artikel, jurnal, dokumen dan literatur terkait. Teknik analisis data kualitatif seperti content analysis, grounded theory, dan thematic analysis digunakan untuk memahami makna dan pola dari data yang dikumpulkan. Artikel ini memberikan pemahaman yang mendalam tentang bagaimana hukum adat Minangkabau diwariskan dan dipraktikkan serta bagaimana pengaruh Kompilasi Hukum Islam dan Kitab Undang-Undang Hukum Perdata terhadap praktik hukum adat Minangkabau. Hasil dari penelitian ini diharapkan dapat memberikan kontribusi bagi pengembangan pemikiran hukum adat Minangkabau dan bagaimana mengintegrasikan hukum adat dengan peraturan perundang-undangan yang berlaku.Kata Kunci: Hukum Adat; Kompilasi Hukum Islam; Kitab Undang-Undang Hukum Perdata